Circulating microRNAs in Medicine - Pozniak, Tetiana; Shcharbin, Dzmitry; Bryszewska, Maria (International journal of molecular sciences, 2022)
Circulating microRNAs (c-microRNAs, c-miRNAs), which are present in almost all biological fluids, are promising sensitive biomarkers for various diseases (oncological and cardiovascular diseases, neurodegenerative pathologies, etc.), and their signatures accurately reflect the state of the body. Studies of the expression of microRNA markers show that they can enable a wide range of diseases to be diagnosed before clinical symptoms are manifested, and they can help to assess a patient’s response to therapy in order to correct and personalize treatments. This review discusses the latest trends in the uses of miRNAs for diagnosing and treating various diseases, viral and non-viral. It is concluded that exogenous microRNAs can be used as high-precision therapeutic agents for these purposes.